2015
DOI: 10.14740/cr377w
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Serum Cystatin C Levels in Newly Diagnosed Acute Myocardial Infarction at the Onset and at the Time of Hospital Discharge

Abstract: BackgroundCystatin C (Cys-C) is a marker of renal damage. Higher serum levels of Cys-C were observed in cardiovascular disease. This study aimed to test the null hypothesis that Cys-C levels in newly diagnosed acute myocardial infarction (AMI) may remain high in the survival and the impact of the cardiometabolic risk factors is small.MethodsForty patients with AMI are enrolled in this study. The cardiometabolic factors including the anthropometric measurements, blood pressure and lipid profile were determined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Those studies suggested that MMP3 enzymatic activity may be more valuable for diagnosis NPC than the protein concentration. Currently, the measurement of enzyme activity in serum/plasma has been employed widely in clinical diagnosis [18][19][20]. However, most of the research focus on the study of MMP3 concentration due to the convenient methods for the quantification of protein concentration by ELISA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those studies suggested that MMP3 enzymatic activity may be more valuable for diagnosis NPC than the protein concentration. Currently, the measurement of enzyme activity in serum/plasma has been employed widely in clinical diagnosis [18][19][20]. However, most of the research focus on the study of MMP3 concentration due to the convenient methods for the quantification of protein concentration by ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the measurement of enzyme activity in serum/plasma has been employed widely in clinical diagnosis 18 - 20 . However, most of the research focus on the study of MMP3 concentration due to the convenient methods for the quantification of protein concentration by ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, high‐circulation cys C may be associated with a strong cardiac inflammatory response, contributing to the development of no‐reflow and the increased risk of death. Second, high cys C levels are highly sensitive markers for mild renal dysfunction . Mild renal dysfunction is associated with microvascular endothelial dysfunction, which may result in poor myocardial perfusion and clinical outcomes …”
Section: Discussionmentioning
confidence: 99%
“…Cys C, produced by all cells with a nucleus, is excreted into blood and freely filtered by the glomerular . Cys C is also released from myocardial cells and hypoxia increases its production .…”
Section: Introductionmentioning
confidence: 99%
“…High Cys-C level is a highly sensitive marker of mild renal insufficiency. Mild renal insufficiency is associated with microvascular endothelial insufficiency [25]. High Cys-C level may lead to microvascular endothelial insufficiency, activate RAAS system, accumulate extracellular matrix, accelerate atrial fibrosis, and activation of RAAS system may also lead to renal function damaged.…”
Section: Discussionmentioning
confidence: 99%